What are the consequences of global banking for the international transmission of shocks? A quantitative analysis - José Luis Fillat Comenge; Stefania Garetto; Arthur V. Smith (Federal Reserve Bank of Boston, 2018)
The global financial crisis of 2008 was followed by a wave of regulatory reforms that affected large banks, especially those with a global presence. These reforms were reactive to the crisis. In this paper we propose a structural model of global banking that can be used proactively to perform counterfactual analysis on the effects of alternative regulatory policies. The structure of the model mimics the US regulatory framework and highlights the organizational choices that banks face when entering a foreign market: branching versus subsidiarization. When calibrated to match moments from a sample of European banks, the model is able to replicate the response of the US banking sector to the European sovereign debt crisis. Our counterfactual analysis suggests that pervasive subsidiarization, higher capital requirements, or ad hoc policy interventions would have mitigated the effects of the crisis on US lending.
Keywords: F12; F23; F36; G21; 330; global banks; banking regulation; shock transmission